Liver Transplantation in Defects of Cholesterol Biosynthesis: The Case of Lathosterolosis. Issue 4 (12th March 2014) - Calvo, P. L.; Brunati, A.; Spada, M.; Romagnoli, R.; Corso, G.; Parenti, G.; Rossi, M.; Baldi, M.; Carbonaro, G.; David, E.; Pucci, A.; Amoroso, A.; et al.
<x xml:space="preserve">Abstract</x> We report the outcome of liver transplantation (LT) in the only surviving patient with lathosterolosis, a defect of cholesterol biosynthesis characterized by high lathosterol levels associated with progressive cholestasis, multiple congenital anomalies and mental retardation. From her diagnosis at age 2 she had shown autistic behavior, was unable to walk unaided and her sight was impaired by cataracts. By age 7 she developed end‐stage liver disease. After a soul‐searching discussion within the transplantation team, she was treated with LT as this represented her only lifesaving option. At 1‐year follow‐up, her lathosterol levels had returned to normal (0.61 mg/dL from 13.04 ± 2.65) and her nutrition improved. She began exploring her environment and walking by holding onto an adult's hand and then independently. Her brain magnetic resonance imaging (MRI) had shown a normal picture at age 1, whereas a volume reduction of white matter with ex vacuo ventricular dilatation and defective myelinization were observed before transplant. At 5‐year follow‐up, a complete biochemical recovery, an arrest of mental deterioration and a stable MRI picture were achieved, with a return to her every day life albeit with limitations. Timely liver transplant in defects of cholesterol biosynthesis might arrest the progression of neurological damage.